HUBUNGAN ANTARA TINGKAT KEHARMONISAN KELUARGA DENGAN KEMATANGAN EMOSI SISWA KELAS XI SMA NEGERI 9 PEKANBARU T.A 2017/2018 - Shandra R Sugianto; Tri Umari; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to determine the level of family harmony, emotional maturity, and the relationship between the level of family harmony and students' emotional maturity. This research is conducted on the students of class XI SMA Negeri 9 Pekenbaru T.A 2017/2018. This research uses corrational method. Data collection techniques used questionnaires. To analyze data using percentage technique and product moment-pearson correlation test. The sample of this study amounted 174 students. The research hypothesis is that there is relationship between family harmony and students' emotional maturity. Data processing is done by manualization and computerized system using SPSS program 24. The result of data processing in getting family harmony level is in good category that is 44,25%, emotional maturity is in medium category that is 66,1%, and there is positive relationship and significant between emotional maturity and family harmony.Keywords: Family Harmony, Emotional Maturity